A Study of Colonization with ESBL and AMPC E Coli in Gut of Patients of Tertiary Care Hospital, Ahmedabad - Sachin M Patel; Nidhi Sood; Parul Patel (Medsci Publications, 2016)
Background: Higher prevalence of ESBL (Extended spectrum betalacamase)-producing E. coli in fecal carriage has been reported in the nosocomial setting than in the community due to high levels of antibiotic consumption. This study is to know the prevalence of ESBL producing E.coli in stool samples of Hospitalized patient with non GIT complains. Material & Methods: A total 300 Stool samples of the patients with non GIT complains  admitted in General Hospital, Sola, Ahmadabad were collected  for study between  December 2012 to March 2013. All samples were tested for routine stool microscopy as well as culture and sensitivity according to NCCLS guideline. Result:  Of 100 samples showing E.coli out of 300 samples, 43% show ESBLs producing E.coli and Amp C producing E.coli show in 26% cases. While 31% was normal E.coli without ESBLs B-lactamase and AmpC B lactamase. Commonest age group is 0-15 years. Conclusion: Our normal gut flora is highly replaced by the ESBLs/AmpC producing E.coli, though they are non pathogenic organism. A threatening epidemiological problem is the dissemination of ESBL-producing organisms to healthy people in the community, which might depend on the frequency of ESBL fecal carriage as well as on the presence of ESBL producing organisms in the food chain.